La géographie humaine et ses cursus au sein des universités belges et européennes - Jean-Marie Halleux; Christophe Breuer (Belgeo)
The research synthesized in this article focuses on university education of human geography. It is based on a comparison of the programs of Bachelor in geography in six countries and it helped to highlight the co-existence of three distinct models: the teaching of a “geography and planning” in France and the Netherlands; the teaching of a “diverse and autonomous geography against planning” in the UK, Germany and Switzerland; the teaching of a “geography by the basic sciences” in Belgium. Given the considerable weight of basic natural sciences in the latter model, Belgium occupies an original position that is not favorable to the growth of human geography. We therefore conclude that it is opportune to reflect on the evolution of the model in question.